Diagnostic and prognostic values of the V-index, a novel ECG marker quantifying spatial heterogeneity of ventricular repolarization, in patients with symptoms suggestive of non-ST-elevation myocardial infarction. (1st June 2017) - Abächerli, Roger; Twerenbold, Raphael; Boeddinghaus, Jasper; Nestelberger, Thomas; Mächler, Patrick; Sassi, Roberto; Rivolta, Massimo W; Roonizi, Ebadollah Kheirati; Mainardi, Luca T; Kozhuharov, Nikola; Rubini Giménez, Maria; Wildi, Karin; et al.
Abstract: Background: The V-index is an ECG marker quantifying spatial heterogeneity of ventricular repolarization. We prospectively assessed the diagnostic and prognostic values of the V-index in patients with suspected non-ST-elevation myocardial infarction (NSTEMI). Methods: We prospectively enrolled 497 patients presenting with suspected NSTEMI to the emergency department (ED). Digital 12-lead ECGs of five-minute duration were recorded at presentation. The V-index was automatically calculated in a blinded fashion. Patients with a QRS duration > 120 ms were ruled out from analysis. The final diagnosis was adjudicated by two independent cardiologists. The prognostic endpoint was all-cause mortality during 24 months of follow-up. Results: NSTEMI was the final diagnosis in 14% of patients. V-index levels were higher in patients with AMI compared to other causes of chest pain (median 23 ms vs. 18 ms, p < 0.001). The use of the V-index in addition to conventional ECG-criteria improved the diagnostic accuracy for the diagnosis of NSTEMI as quantified by area under the ROC curve from 0.66 to 0.73 (p = 0.001) and the sensitivity of the ECG for AMI from 41% to 86% (p < 0.001). Cumulative 24-month mortality rates were 99.4%, 98.4% and 88.3% according to tertiles of the V-index (p < 0.001). After adjustment for age and important ECG and clinical parameters, the V-index remained an independent predictor of death. Conclusions: The V-index, an ECG marker quantifying spatial heterogeneity of ventricular repolarization, significantly improves the accuracy and sensitivity of the ECG for the diagnosis of NSTEMI and independently predicts mortality during follow-up.